The correlation between initial velocity and jumping ability in Taiwanese adolescent track and field athletes (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
The correlation between initial velocity and jumping ability in Taiwanese adolescent track and field athletes